Sensitivity of ant (Cephalotes) colonies and individuals to antibiotics implies feeding symbiosis with gut microorganisms - Jaffe, K.; Caetano, F. H.; Sanchez, P.; Hernandez, J.; Caraballo, L.; Vitelli-Flores, J.; Monsalve, W.; Dorta, B.; Lemoine, V. R. (Natl Research Council Canada, 2001)
Ants in the tribe Cephalotini are exceptional in that they maintain microorganisms in their digestive tract. To understand what these microorganisms mean to the ants, we observed the feeding habits of Cephalotes pusillus and Cephalotes atratus, finding that in nature they feed on extrafloral nectars, homopteran secretions, and bird droppings. Feeding the antibiotic kanamycin to colonies of C. pusillus in the laboratory kills them. Ants desiccate or starve rather than feed on liquids to which the antibiotics gentamycin and netilmycin have been added, but feed and survive on liquids containing nystatin, penicillin, and ampicillin. We identified over 10 microorganisms from the intestine of C. pusillus with different antibiotic-resistance patterns. The bacteria are from the genera Corynebacterium, Brevibacterium, Sphingobacterium, Ochrobactrum, Myroides, Brevundimonas, Alcaligenes, Stenotrophomonas, Moraxella, and Pseudomonas. We hypothesize that the microorganisms provide nutrients to the ants by synthesizing amino acids from carbohydrates and nitrates. We do not know whether the ants collect the bacteria from the environment, but they transmit them to their young. They culture them in their digestive tract, eventually feeding on them.